Minor Nuisance Around Foreign Exchange Markets - Lessons from the Stability and Growth Pact Debate - Matthias Bauer; Martin Zenker (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2012)
This paper studies the impact of political events that systematically undermined the Stability and Growth Pact (SGP) on the euro's foreign exchange expectation bias for the period 2001 to 2005. Our findings suggest that euro foreign exchange markets were attentive to the political dispute over the enforcement of the SGP's rules. The results indicate that foreign exchange markets anticipated the gradual demise of the SGP. 1) For the expectation bias in euro foreign exchange markets we do not find systematic level effects. 2) Since volatility decreases following 'destabilising' political events, we conclude that already in the early years of the SGP regime the demise of the original Pact was anticipated by foreign exchange market participants. The conclusion is that a politicised multilateral fiscal rule does not improve market discipline, which could be a crucial argument against the new 'European Fiscal Compact'.
urn:nbn:de:gbv:27-20131119-151122-3
Keywords: E62; F31; F33; C22; C58; 330; fiscal rules; market discipline; FX markets; GARCH; Wechselkurs; Erwartungstheorie; Euro; Europäischer Stabilitätsmechanismus; Politische Stabilität; Eurozone